Ages of Jericho and Their Importance for the Biblical Chronology - Chirilă, Ioan (Sacra scripta, 2003)
The setting up of Jericho's chronological landmarks brings light on the entire Ancient Testament’s chronology which orbits around the Exodus’ events. Jericho is, for the allegorical exegesis, the gate of hope, the clear sign of the fulfillment of the promises made to the patriarchs. Our attention must be focused on the city’s fourth level, extensively studied by J. Garstang and K. Kenyon, who establish as a possible chronological landmark for the return to Canaan the years between 1400 – 1388 BC. There are many ideas concerning the fall of Jericho’s walls. Both Garstang and Kenyon found evidence of earthquake activities at the time the city met its end. If God did use an earthquake to accomplish His purposes that day, it was still a miracle since it had happened at the right moment, and was manifested in such a way in order to protect Rahab’s house. No matter what means God did use, it was His work, through the faith of the Israelites led by Joshua, that brought the walls down. After the people surrounded the city and marched around its walls for seven days, it was “by faith the walls of Jericho fell down” (Hebrews 11: 30).